Calidad del agua en el tramo bajo del río Negro (Chaco, Argentina) - Poi, Alicia Susana G. (2003)
Water quality in the lower stretch of the Negro River (Chaco, Argentine). The main physical, chemical and biological characteristics of surface waters were measured between November 1999 and May 2002 in four sampling sites located in the course of Negro River. At sites 1 and 2 wetlands and alluvial forest with low human occupation characterize the bordering landscape. Sites 3 y 4 were affected by domestic and industrial discharges, although in the last years tannin production was working at a reduce volume. The chemical composition of surface water was derived primarily from the rain seasonality and the wash-out of salt rich wetlands soil into the river channel. Conductivity was higher during the dry period than the rain period. Salinity varied between 82.7 mg.1-1 and 6500 mg.l-1. The mean concentration of total phosphorus was high (1053 µg.l-1) and pH was neutral or slightly alkaline. At site 4, organic matter content (COD = 385 mg.l-l ) increased significantly during the low water period. There were not found residues of 27 pesticides and organochlorine compounds on bottom sediments at sampling sites. Cadmium (Cd) and lead (Pb) content in bottom sediments fell below the detection limits. Chromium (Cr) content varied between 14 and 22 µg. g dry weight depending on study sites. Ten species of aquatic plants were collected at Site 1, which is characterized by low flow velocities. The macrophytes species richness decreased downstream. The occurrence of some macrophytes species such as Hydrocotyle ranunculoides and Ceratophyllum demersum was related to significant phosphorus availability. Chlorophyll a concentration, as indicator of phytoplankton biomass, was low at all study sites (minor than 20 µg.l-1).